Tumor and α‐SMA‐expressing stromal cells in pancreatic neuroendocrine tumors have a distinct RNA profile depending on tumor grade - Helvijs Niedra; Raitis Peculis; Rihards Saksis; Ilona Mandrika; Sofija Vilisova; Jurijs Nazarovs; Austra Breiksa; Aija Gerina; Julie Earl; Ignacio Ruz‐Caracuel; Marta Gabriela Rosas; Aldis Pukitis; et al. (Molecular Oncology)
Alpha‐smooth muscle actin (α‐SMA) expression in the stroma is linked to the presence of cancer‐associated fibroblasts and is known to correlate with worse outcomes in various tumors. In this study, using a GeoMx digital spatial profiling approach, we characterized the gene expression of the tumor and α‐SMA‐expressing stromal cell compartments in pancreatic neuroendocrine tumors (PanNETs). The profiling was performed on tissues from eight retrospective cases (three grade 1, four grade 2, and one grade 3). Selected regions of interest were segmented geometrically based on tissue morphology and fluorescent signals from synaptophysin and α‐SMA markers. The α‐SMA‐expressing stromal‐cell‐associated genes were involved in pathways of extracellular matrix modification, whereas, in tumor cells, the gene expression profiles were associated with pathways involved in cell proliferation. The comparison of gene expression profiles across all three PanNET grades revealed that the differences between grades are not only present at the level of the tumor but also in the α‐SMA‐expressing stromal cells. Furthermore, the tumor cells from regions with a rich presence of adjacent α‐SMA‐expressing stromal cells revealed an upregulation of matrix metalloproteinase‐9 (MMP9) expression in grade 3 tumors. This study provides an in‐depth characterization of gene expression profiles in α‐SMA‐expressing stromal and tumor cells, and outlines potential crosstalk mechanisms.